The Influence of Rewards and Punishments on the Performance of Employees: JEL Classification: M12, M52, J24, J28, L32 - Rahmi Nursanda; Mujahid Yunus; Abdul Samad Arief (Journal La Bisecoman, 2026)
This study aims to determine and analyze each reward and punishment variable that has a positive and significant effect on the performance of employees at the Makassar Region V Airport Authority Office. This research was conducted at the Makassar Airport Authority Region V Office on Airport Authority Road Number 5, Maros. Data collection used a questionnaire. Data processing used a computer application, namely the Statistical Package of Social Sciences (SPSS) version 26. The results of this study indicate that both independent variables (reward and punishment) have a positive influence on the dependent variable (employee performance). The results of this study provide an overview that the rewards and punishments carried out by the Makassar Region V Airport Authority Office organization provide little information needed to predict the Employee Performance variable. Thus, the appropriate implementation of rewards and punishments can serve as an effective strategy to improve employee performance. Organizations are expected to continuously evaluate and refine their reward and sanction systems in order to create a productive work environment that is oriented toward achieving organizational goals optimally.